The impact of pancreas compression time during minimally invasive gastrectomy on the postoperative complications in gastric cancer. Issue 6 (14th July 2021) - Itamoto, Kota; Hikage, Makoto; Fujiya, Keiichi; Kamiya, Satoshi; Tanizawa, Yutaka; Bando, Etsuro; Terashima, Masanori
Abstract: Aim: Pancreas compression during minimally invasive gastrectomy causes blunt injury to the pancreas and leads to postoperative complications. However, the extent of practical compression associated with the incidence of postoperative complications remains unknown. This study aimed to evaluate the impact of pancreas compression, particularly the duration of compression, on short‐term outcomes in minimally invasive gastrectomy for gastric cancer. Methods: This study included 178 patients who underwent laparoscopic or robotic gastrectomy at the Shizuoka Cancer Center in 2018. The total time of pancreas compression during gastrectomy was measured using video‐reviews, and the correlation between the time and surgical outcomes was evaluated. Results: A duration of 3 min was selected as the cutoff value of pancreas compression time to predict high drain amylase concentration on postoperative day 1 (≥1000 U/L). The incidence of clinically relevant pancreatic fistula (1.5% vs 12.4%, P  = .011) and all postoperative complications (12.3% vs 30.1%, P  = .010) were significantly higher in the longer‐compression group than in the shorter‐compression group. The multivariable analysis identified longer compression as the only independent risk factor for postoperative complications. Conclusion: More than a few minutes of pancreas compression during minimally invasive gastrectomy was associated with a higher incidence of postoperative complications. Abstract : This retrospective study aimed to clarify the influence of pancreas compression, with special attention on the duration of compression on the short‐term outcomes in patients who received minimally invasive gastrectomy. We assessed 178 patients who underwent laparoscopic or robotic gastrectomy at the Shizuoka Cancer Center in 2018. The cutoff value of pancreas compression time for the prediction of blunt injury of pancreas was found to be 3 min, and the incidence of postoperative complications was significantly higher in patients with longer‐compression than in those with shorter‐compression.